Distinct stages during colonization of the mouse gastrointestinal tract by Candida albicans - Prieto, Daniel; Pla, Jesús (Frontiers in Microbiology, 2015)
Candida albicans is a member of the human microbiota, colonizing both the vaginal and gastrointestinal tracts. This yeast is devoid of a life style outside the human body and the mechanisms underlying the adaptation to the commensal status remain to be determined. Using a model of mouse gastrointestinal colonization, we show here that C. albicans stably colonizes the mouse gut in about 3 days starting from a dose as low as 100 cells, reaching steady levels of around 107 cells/g of stools. Using fluorescent labeled strains we have assessed the competition between isogenic populations from different sources in cohoused animals. We show that long term (15 days) colonizing cells have increased fitness in the gut niche over those grown in vitro or residing in the gut for 1-3 days. Therefore, two distinct states, proliferation and adaptation, seem to exist in the adaptation of this fungus to the mouse gut, a result with potential significance in the prophylaxis and treatment of Candida infections.